Individualistic and supra-individualistic predictors of optimal social rehabilitation impact on offenders under non-custodial supervision - Andrzej Bałandynowicz (Maria Curie-Skłodowska University, Lublin, Poland, 2017)
The meeting that reaches the boundaries of dialogical moments (dialogical i.e. reaching the depth in interpersonal communication) may be an identity-creative situation i.e. the situation in which the identity of participants is acted, learnt, and experienced. The most important conditions which enable us to make a full dialogue are: the kinds of relationships between participating parties, attention and mutual understanding, and love. Interpersonal relations differ in the number of participants, in their depth, character, intensity in time, and may signal the type of a meeting. In the context of philosophical anthropology of Teilhard de Chardin, B. Pasamonik presents the process of communication as a relation of utilitarian character, oriented towards achieving something, and as a personalist relation whose aim is to "meet somebody". In the latter, there is no clearly cognitive aim that would reduce "the Other" to the object of cognition; it is rather about the possibility of communing, being opened to another person, which is possible only in the case of a relationship based on responsibility.